Aplikasi Mobile Berbasis Flutter Untuk Optimasi Manajemen Peternakan Babi Skala Perorangan - Ade Astrawijaya; Yuli Asriningtias (Bulletin of Computer Science Research, 2025)
Small-scale pig farming in Indonesia continues to face challenges such as unstructured manual record-keeping, limited health monitoring, and the lack of integration between inventory and financial data. This study aims to develop PigFarm Manager, a mobile-based information system that integrates livestock management, inventory, financial records, and task monitoring into a single digital platform. The system was developed iteratively using the Prototyping method, with Flutter implemented on the frontend, Golang on the backend, and MySQL as the database. System evaluation was conducted using Black Box Testing and Usability Testing (UAT) to ensure that the application’s functionalities meet user needs. The results show that all major features including user authentication, livestock data management, financial transactions, and additional functions such as QR Code scanning and financial report export to Excel, performed well and operated stably. The implementation of the system enables real-time data access, improves recording efficiency, and enhances the accuracy of decision-making at the smallholder level. This is supported by a functional testing success rate of 100% and a usability score of 86%. The study contributes to the digital transformation of the livestock sector by offering a mobile-first solution that is adaptive, efficient, and accessible for small-scale pig farmers.